(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research aims to analyze the role of job satisfaction as a mediating variable in the influence of transformational leadership and work engagement on teachers’ Organizational Citizenship Behavior (OCB). The study used a quantitative, survey-based approach. The selected sample was 101 teachers through a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM). The results of the study indicate that: transformational leadership does not have a positive effect on OCB; transformational leadership does not have a positive effect on job satisfaction; work engagement has a positive effect on job satisfaction; Job satisfaction has a positive effect on OCB; work engagement has a positive effect on OCB; job satisfaction does not mediate the relationship between transformational leadership and OCB; and job satisfaction mediates the relationship between work engagement and OCB. These results indicate that the OCB of teachers at Al Azhar Cilacap School is not influenced by transformational leadership, but rather by other factors not examined in this study.